Prevalence and burden of illness of treated hemolytic neonatal hyperbilirubinemia in a privately insured population in the United States - Tzy-Chyi Yu; Chi Nguyen; Nancy Ruiz; Siting Zhou; Xian Zhang; Elaine A. Böing; Hiangkiat Tan (BMC, 2019)
Abstract Background Prevalence of hemolytic neonatal hyperbilirubinemia (NHB) is not well characterized, and economic burden at the population level is poorly understood. This study evaluated the prevalence, clinical characteristics, and economic burden of hemolytic NHB newborns receiving treatment in U.S. real-world settings. Methods This cohort study used administrative claims from 01/01/2011 to 08/31/2017. The treated cohort had hemolytic NHB diagnosis and received phototherapy, intravenous immunoglobulin, and/or exchange transfusions. They were matched with non-NHB newborns who had neither NHB nor related treatments on the following: delivery hospital/area, gender, delivery route, estimated gestational age (GA), health plan eligibility, and closest date of birth within 5 years. Inferential statistics were reported. Results The annual NHB prevalence was 29.6 to 31.7%; hemolytic NHB, 1.8 to 2.4%; treated hemolytic NHB, 0.46 to 0.55%, between 2011 and 2016. The matched analysis included 1373 pairs ≥35 weeks GA. The treated hemolytic NHB cohort had significantly more birth trauma and hemorrhage (4.5% vs. 2.4%, p = 0.003), vacuum extractor affecting newborn (1.9% vs. 0.8%, p = 0.014), and polycythemia neonatorum (0.8% vs. 0%, p = 0.001) than the matched non-NHB cohort. The treated hemolytic NHB cohort also had significantly longer mean birth hospital stays (4.5 vs. 3.0 days, p < 0.001), higher level 2-4 neonatal intensive care admissions (15.7% vs. 2.4, 15.9% vs. 2.8 and 10.6% vs. 2.5%, respectively, all p < 0.001) and higher 30-day readmission (8.7% vs. 1.7%, p < 0.001). One-month and one-year average total costs of care were significantly higher for the treated hemolytic NHB cohort vs. the matched non-NHB cohort, $14,405 vs. $5527 (p < 0.001) and $21,556 vs. $12,986 (p < 0.001), respectively. The average costs for 30-day readmission among newborns who readmitted were $13,593 for the treated hemolytic NHB cohort and $3638 for the matched non-NHB cohort, p < 0.001. The authors extrapolated GA-adjusted prevalence of treated hemolytic NHB in the U.S. newborn population ≥ 35 weeks GA and estimated an incremental healthcare expenditure of $177.0 million during the first month after birth in 2016. Conclusions The prevalence of treated hemolytic NHB was 4.6-5.5 patients per 1000 newborns. This high-risk hemolytic NHB imposed substantial burdens of healthcare resource utilization and incremental costs on newborns, their caregivers, and the healthcare system.